2012
DOI: 10.1111/j.1365-2613.2012.00814.x
|View full text |Cite
|
Sign up to set email alerts
|

Adverse effects of the anabolic steroid, boldenone undecylenate, on reproductive functions of male rabbits

Abstract: This study was conducted to evaluate the adverse effects of the anabolic steroid, boldenone undecylenate (BOL) on reproductive functions of male rabbits. Thirty white New Zealand mature male rabbits were divided into three groups (10 rabbits each). Group A rabbits served as a control group. Group B rabbits received 4.4 mg/kg body weight (bwt) BOL 5% oily solution. Group C rabbits received 8.8 mg/kg bwt BOL. Rabbits were injected intramuscularly twice weekly for two months. BOL had no significant effect on the … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

3
14
0
2

Year Published

2016
2016
2022
2022

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 26 publications
(19 citation statements)
references
References 28 publications
3
14
0
2
Order By: Relevance
“…Our results were similar to those reported by Ciocca (2005) in athletes and Cannizzo et al (2007) in veal calves. Also, our results agree with Oda and El-Ashmawy (2012) and Thabet et al (2010) who reported that there was a significant reduction in the sperm motility and count after boldenone injections while no abnormalities were detected in the sperm morphology after boldenone injections. According to results from the CASA analysis, different motility patterns were identified after Equigan injection.…”
Section: Discussionsupporting
confidence: 93%
See 1 more Smart Citation
“…Our results were similar to those reported by Ciocca (2005) in athletes and Cannizzo et al (2007) in veal calves. Also, our results agree with Oda and El-Ashmawy (2012) and Thabet et al (2010) who reported that there was a significant reduction in the sperm motility and count after boldenone injections while no abnormalities were detected in the sperm morphology after boldenone injections. According to results from the CASA analysis, different motility patterns were identified after Equigan injection.…”
Section: Discussionsupporting
confidence: 93%
“…In agreement with our findings, Purkayastha and Mahanta (2012) reported a significant decrease in the FSH, LH and testosterone levels after nandrolone decanoate injections in mice. These results agree also with Mohammed et al (2016), Oda and El-Ashmawy (2012) and Thabet et al (2010) who reported a significant reduction in the total testosterone after boldenone injections. In contrast, administration of testosterone alone to bull calves did not induce any variation in testosterone (Simontacchi et al, 2004).…”
Section: Discussionsupporting
confidence: 92%
“…Our results agreed with Tousson et al [4] who reported that intramuscular injection with boldenone in rabbit has negative effect spermatogenesis and many of histopathological alternations in testes. The testicular lesions were similar to those described by Thabet et al [23] and Oda and El-Ashmawy [22]. Cannizzo et al [27] suggested that most of the histopathological changes seen in testis can be explained by estradiol, this was confirmed by the increase in estradiol level recorded in the present study.…”
Section: Discussionsupporting
confidence: 92%
“…Oda and. El-Ashmawy [22] and Thabet et al [23] who reported that; a significant reduction in the sperm motility and count after boldenone injections while no abnormalities were detected in the sperm morphology after boldenone injections. Cell damage occurs when there is an excess of reactive species derived from oxygen and nitrogen, or a defect of antioxidant molecules [24].…”
Section: Discussionmentioning
confidence: 99%
“…Application of anabolic steroids leads to testicular derivatives (Hall and Hall 2005). This testicular atrophy (reduction in testes size in relation to carcass weight) could result from suppressed testosterone production (Cannizzo et al 2007, Oda andEl-Ashmawy 2012). On the other hand, Tawfeek et al (1994) reported that the difference in the testicular weight between the control and injected groups of rabbits was not affected by testosterone injection.…”
Section: Discussionmentioning
confidence: 98%